2022
DOI: 10.1155/2022/4811144
|View full text |Cite
|
Sign up to set email alerts
|

Cloning and Prokaryotic Expression of Carotenoid Cleavage Dioxygenases from Mulberry (Morus notabilis)

Abstract: Carotenoid cleavage dioxygenase (CCD) is the key enzyme for carotenoid cleavage, and the products of carotenoid cleavage regulate the ability of plants to stress. In this paper, six CCD genes were obtained from Morus notabilis (Mn) by reverse transcription-polymerase chain reaction (RT-PCR) and we classified them into three subgroups based on gene structures and phylogenetic analysis. The CDS (coding sequence) regions of the six MnCCD genes were 1617, 1620, 1635, 1713, 1746, and 1791 bp in full length, encodin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 28 publications
0
0
0
Order By: Relevance
“…Most of the ChCCOs contained four histidine active sites, which might be closely related to their iron-binding abilities [28,29]. Subcellular localization analysis revealed that ChCCOs were mainly localized in cytoplasm and chloroplast, which was consistent with the CCOs from many other plant species [13,[30][31][32]. Synteny analysis revealed that ChCCD-like-a and ChCCD-like-b were tandem duplicated genes, suggesting that the tandem duplication of CCD-like subfamily members contributed to the amplification of the CCO gene family in C. humilis.…”
Section: Discussionsupporting
confidence: 68%
“…Most of the ChCCOs contained four histidine active sites, which might be closely related to their iron-binding abilities [28,29]. Subcellular localization analysis revealed that ChCCOs were mainly localized in cytoplasm and chloroplast, which was consistent with the CCOs from many other plant species [13,[30][31][32]. Synteny analysis revealed that ChCCD-like-a and ChCCD-like-b were tandem duplicated genes, suggesting that the tandem duplication of CCD-like subfamily members contributed to the amplification of the CCO gene family in C. humilis.…”
Section: Discussionsupporting
confidence: 68%